A concise history of Sunnis & Shi'is - McHugo, John, 1951- (Georgetown University Press, 2017)
A fascinating and richly layered account of how and why the great divide in Islam--between Sunnis and Shi'is--occurred. Charting the history of Islam from the death of the Prophet Mohammed to the present day, McHugo describes the conflicts that raged over the succession to the Prophet, how Sunnism and Shi'ism evolved as different and contending sects during the Abbasid caliphate, and how the rivalry between the empires of the Sunni Ottomans and Shi' Sfavids ensured that the split would continue into the modern age. Today the full, destructive force of this historical conflict for the soul of the Muslim world is expressed by the struggle between Saudi Arabia and Iran--with no end in sight. Definitive, insightful, and accessible, A Concise History of Sunnis and Shi'is is an essential guide to understanding the genesis, development, and manipulation of the schism that has come to define Islam and the Muslim world. Includes five black & white maps, a glossary, and a list of sources and further reading.